Factors associated with physical inactivity among health staff in a government department in Putrajaya - Zakariah, Nurhaliza (2017)
Introduction: Physical inactivity has been recognized as the fourth leading risk factor for mortality worldwide. Individuals who are physically inactive has increased risk 20% to 30% to die prematurely. Individuals who fulfil the minimum recommendation of physical activity can prevent the development of noncommunicable diseases. In 2015, 33.5% of the Malaysian adults were reported to be physically inactive. Various factors are found to be associated with physical inactivity participation and these factors need to be explored.